The Influence of Advertising and Servicescape on Interest in Continuing Studies with Brand Image as a Mediation Variable in Master of Management Mahasaraswati Denpasar University - Luh Kemala Putri Widhiari; I Gusti Agung Eka Teja Kusuma; Putu Kepramareni (Advances in Global Economics and Business Journal, 2021)
Education has a primary role in the national development agenda during the development period to achieve progress in the social, cultural, political, and economic fields. Globalization has encouraged the emergence of very competitive competition in education, both among State Universities and Private Universities, one of which is Mahasaraswati Denpasar University, especially the Master of Management study program. It was recorded that from 2015 to 2019, there was a significant inequality, as many factors influenced one’s interest in continuing their studies or not their studies. One of the factors is buying interest in educational services. In this study, the number of samples was 272 respondents using the Slovin formula. The sampling method was the stratified random sampling technique. Methods of collecting data were interviews and questionnaires. The data analysis technique was performed using Path Analysis (Structural Equation Modeling-Partial Least Square (SEM PLS). The findings reveal that out of seven hypotheses, six hypotheses are accepted.